The decomposition and efficiency of NPK-enriched biochar addition on Ultisols with soybean - Sugeng Winarso; Marga Mandala; Hari Sulistiyowati; Sukron Romadhona; Bambang Hermiyanto; Wachju Subchan (Universitas Sebelas Maret, 2020)
This research aims to compare fresh biochar and NPK-enriched biochar and their decomposition levels and nutrient absorption efficiency in acid soil with soybean. Factorial randomized block design was used in this experiment and consisted of two factors. The first factor, biochar source, comprised four levels: B0: biochar without NPK, B1: rice straw biochar + NPK, B2: soybean straw biochar + NPK, and B3: wood biochar + NPK. The second factor, biochar enrichment, comprised four levels: D1: 0.5 tons ha-1, D2: 2.5 tons ha-1, D3: 5.0 tons ha-1, and D4: 10 tons ha-1. Each treatment was replicated three times, yielding 48 experiment units. The results showed that biochar enrichment with NPK affected the decomposition level. The percentage of increasing decomposition in enriched wood biochar (0.09%) was lower than rice (0.28%) and soybean (0.53%) straw biochar. An increase in NPK absorbance efficiency and soybean dry weight was evident in NPK-enriched biochar. The highest N absorbance efficiency occurred in wood biochar (21%), followed by soybean and rice straw biochar, respectively, while the highest P and K absorbances were found in rice straw biochar (35% and 26%, respectively), followed by wood and then soybean biochar.